«Lighting price» of cucumber yield in the winter-spring turnover of greenhouses - A. V. Kurepin; A. F. Pershin; V. N. Shevkunov (Овощи России, 2021)
Relevance. Among the main factors that determine the productivity of vegetable yields in protected ground, the main one is light. For the formation of 1 kg/m2 of cucumber fruits with a length of 18-22 cm, on average about 3500-4000 J/cm2 of solar radiation is required. In the winter-spring cycle, in the absence of artificial lighting in greenhouses, there is an unevenness of scattered solar radiation and a general shortage of incoming light energy. At the same time, the amount of total solar radiation required for the formation of a 1 kg of fruit ("lighting price") is not the same for different hybrids. To increase the profitability of production in the winter-spring turnover in greenhouses that are not equipped with artificial lighting, it is necessary to choose hybrids with the lowest "lighting price" of the crop, that is, hybrids that use less light energy to form a 1 kg of fruit.The purpose of the study: evaluation of F1 hybrids of cucumber on the basis of resistance to lack of lighting by comparing their "lighting price" of the crop: how much energy is spent on the formation of 1 kg of marketable products.Methods. The research was carried out at the variety testing site in the Crimean breeding Center of the Scientific Research Institute of Vegetable Crop Selection "Gavrish", in the conditions of winter-spring turnover, in greenhouses not equipped with artificial lighting. We tested seven medium-fruited (18-22 cm) spined-fruited cucumber hybrids recommended for growing in winter-spring turnover.Results. The analysis of the data on the input of solar radiation and the formation of a standard yield showed that there is a direct relationship between the amount of incoming light and the level of productivity. The period of conversion of the received solar energy into the fruit harvest varied during the growing season from 14 to 8 days, depending on the degree of plant development. The "lighting price" of the crop was not the same for different hybrids: the hybrids tested in the experiment spent an average of 2900 J/cm2 per 1 kg of product, which is 18% more efficient than for standard greenhouse cucumbers.